The arrangement of information in the general bilingual dictionary entry. - van Scherrenburg, Daniel. (University of Ottawa (Canada), 1990)
One topic that has not been dealt with extensively in the literature on bilingual lexicography and in the front matter of general bilingual dictionaries (GBDs) is the arrangement of information within the GBD entry. Thus, I have endeavoured to present in one work various arrangement techniques for seven important GBD entry elements: the equivalent, the meaning, the context, the meaning discrimination device, the example, the idiom and the compound. It is hoped that by providing a clear description of possible arrangement techniques for these elements, this thesis will not only provide lexicographers with further insight into bilingual dictionary methodology, but also help dictionary-users to better appreciate some of the problems faced by bilingual lexicographers.
Keywords: Library Science.